A high-strength, high-plasticity copper-rich high-entropy alloy and its preparation method and application

By preparing high-strength, high-plastic, rich copper and high-entropy alloys with FCC+BCC biphasic structure, the existing high-entropy alloys have been solved, and the problems of high-strength, good plasticity and excellent corrosion resistance are achieved, and advanced ships have demand for propeller thrust.

CN116083775BActive Publication Date: 2025-03-25UNIV OF SCI & TECH BEIJING
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211664967.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2025-03-25
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

The existing Fe-Co-Cr-Ni-based high-entropy alloys have high cost and are not resistant to biofouling, and the copper alloys have poor corrosion resistance and low strength, which cannot meet the demand for propeller thrust by advanced ships.

Method used

A high-strength and high-plastic copper-rich high-entropy alloy is used, with the chemical formula of CuaNibMncFedCreAlf, in which 40≤a≤55at%, 20≤b≤30at%, 5≤c≤15at%, 3≤d≤8at%, 3≤e≤8at%, and 4≤f≤12at%. It is prepared by vacuum medium frequency induction smelting, cold rolling, crystallization annealing and water quenching, and a high-entropy alloy with FCC+BCC biphasic structure is formed.

Benefits of technology

It achieves high strength, good plasticity and excellent corrosion resistance of marine biological pollution. The yield strength can reach 831MPa and the elongation can reach 33%, which significantly improves the resistance to seawater corrosion of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116083775B_ABST
    Figure CN116083775B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of metal materials, and specifically relates to a high-strength, high-plasticity copper-rich high-entropy alloy and its preparation method and application. The chemical formula of the high-entropy alloy is: Cu a Ni b Mn c Fe d Cr e Al f , wherein 40≤a≤55at%, 20≤b≤30at%, 5≤c≤15at%, 3≤d≤8at%, 3≤e≤8at%, 4≤f≤12at%, and a+b+c+d+e+f=100%. The preparation process of the high entropy alloy mainly includes: smelting of master alloy; cold rolling with a deformation amount of 40%-60%; recrystallization treatment at 900-1000°C and aging treatment at 400-500°C. The high-strength and high-plasticity copper-rich high-entropy alloy of the present invention has excellent tensile strength and plasticity, resistance to corrosion of 3.5wt.% NaCl solution and copper ion seepage ability, and has broad application prospects in the fields of marine industry and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of metal materials, and specifically relates to a high-strength, high-plasticity copper-rich high-entropy alloy, and a preparation method and application thereof. Background Art

[0002] Traditional alloy design relies on modifying properties by adding trace elements to one or two primary elements. The concept of high-entropy alloys, introduced in the early 20th century, offered a new approach to alloy design. Their multi-principal component composition creates a high mixing entropy effect, stabilizing solid solution formation and reducing the likelihood of intermetallic compound precipitation. This favors the formation of simple solid solution structures, such as single-phase or multi-phase face-centered cubic (FCC), body-centered cubic (BCC), or hexagonal close-packed (HCP). Existing research on high-entropy alloys has demonstrated excellent comprehensive mechanical properties and corrosion resistance.

[0003] For metal materials used in marine environments, not only excellent mechanical properties and electrochemical corrosion resistance are required, but also resistance to biofouling and corrosion. Marine biofouling mainly refers to the formation of corrosive metabolites by marine organisms such as algae, barnacles, and mollusks (oysters and mussels) in seawater, which attach to the material to form biofilms, have an adverse effect on the surface of the material, and as time goes by, they will also corrode the inside of the material, thereby affecting the service life of the material. Cu ions are heavy metal ions with certain toxic effects. They can effectively kill marine organisms such as barnacles, shellfish, and oysters to prevent them from adhering to the surface of the material. Therefore, at present, marine environment metal components such as ship propellers and pumps, valves, and underwater fasteners are mainly made of copper alloys (typical nickel-aluminum bronze composition: Cu 81 Al9Fe4Ni4Mn2). However, due to the complex structure of nickel-aluminum bronze alloy, there are mainly β phase, γ phase, α phase and κ phase, among which κ phase has many forms, including κ Ⅰ , κ Ⅱ , κ Ⅲ , κ Ⅳ Phases, each with different potentials, make the alloy highly susceptible to electrochemical corrosion. Furthermore, the alloy's poor strength and ductility make it unable to meet the propeller thrust requirements of modern advanced ships. Therefore, there is an urgent need to develop an alloy that combines high corrosion resistance, resistance to marine biofouling, and excellent comprehensive mechanical properties.

[0004] Current research on copper-containing high-entropy alloys mainly focuses on high-entropy alloys with low copper content and high-entropy alloys with only compressive plasticity (structural materials for industrial applications usually require tensile plasticity). Summary of the Invention

[0005] The present invention aims to provide a high-strength and high-plasticity copper-rich high-entropy alloy and its preparation method and application, so as to solve the problems of high cost and poor resistance to biofouling of existing Fe-Co-Cr-Ni high-entropy alloys, as well as the problems of poor corrosion resistance and low strength of copper alloys.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a high-strength and high-plasticity copper-rich high-entropy alloy, the chemical formula of which is: Cu a Ni b Mn c Fe d Cr e Al f , among which, 40≤a≤55at%, 20≤b≤30at%, 5≤c≤15at%, 3≤d≤8at%, 3≤e≤8at%, 4≤f≤12at%, and a+b+c+d+e+f=100%.

[0007] Furthermore, the chemical formula of the high entropy alloy is: Cu a Ni b Mn c Fe d Cr e Al f , among which, 40≤a≤50at%, 20≤b≤30at%, 6≤c≤10at%, 4≤d≤6at%, 4≤e≤6at%, 6≤f≤10at%, and a+b+c+d+e+f=100%.

[0008] Furthermore, when a=46, b=24, c=10, d=5, e=5, f=10, the chemical formula of the high entropy alloy is: Cu 46 Ni 24 Mn 10 Fe5Cr5Al 10 The alloy has a yield strength of 329 MPa, a tensile strength of 648 MPa, and an elongation of 33%.

[0009] Furthermore, when a=50, b=24, c=10, d=5, e=5, f=6, the chemical formula of the high entropy alloy is: Cu 50 Ni 24 Mn 10 Fe5Cr5Al6, the alloy has a yield strength of 468Mpa, a tensile strength of 775MPa, and an elongation of 30%.

[0010] Furthermore, when a=48, b=24, c=10, d=5, e=5, f=8, the chemical formula of the high entropy alloy is: Cu 48 Mn 10 Ni 24Fe5Cr5Al8, the alloy has a yield strength of 606Mpa, a tensile strength of 831MPa, and an elongation of 13.7%.

[0011] Another object of the present invention is to provide a method for preparing the above-mentioned high entropy alloy, which specifically comprises the following steps:

[0012] S1) weighing each raw material according to the designed ratio and pre-treating them for later use;

[0013] S2) putting the raw materials processed in S1) into a vacuum medium frequency induction melting furnace and evacuating the furnace to 1×10 -2 Pa below, smelting is carried out in an argon protective environment;

[0014] S3) After vacuum melting, use a crucible or a water-cooled copper mold to cast or suction cast the as-cast high entropy alloy, or a sample component of the desired shape and size;

[0015] S4) cold rolling the as-cast high-entropy alloy in S3) to control the thickness deformation, then performing crystallization annealing, and finally taking it out and water quenching to obtain a high-strength and high-plasticity copper-rich high-entropy alloy.

[0016] Furthermore, the step S4) further comprises: performing an aging treatment on the recrystallized high entropy alloy, and then taking it out for air cooling or water quenching to obtain a high-strength and high-plasticity copper-rich high entropy alloy;

[0017] The temperature of the aging treatment is 400-500° C., and the holding time is 4-24 hours.

[0018] Furthermore, the specific process of S1) is as follows: S1.1) firstly, the Cu, Ni, Mn, Fe, Cr, and Al metal raw materials are mechanically ground to remove oxide scales on the surface of the elements;

[0019] S1.2) The metal raw material treated in S1.1) is placed in different containers and an alcohol solution is added thereto. The metal raw material is ultrasonically cleaned and then taken out and dried with the alcohol to obtain the ultrasonically treated metal raw material.

[0020] Furthermore, the thickness deformation of the cold rolling in S4) is 40-60%; the annealing temperature is 900-1000° C. and the temperature is maintained for 0.5-4 hours.

[0021] Furthermore, the high-strength and high-plasticity copper-rich high-entropy alloy has an FCC+BCC dual-phase structure, a yield strength of 329 MPa, a tensile strength of up to 831 MPa, and an elongation of up to 33%.

[0022] A high-strength, high-plasticity copper-rich high-entropy alloy used in fields such as marine industry.

[0023] The present invention relates to a high-strength and high-plasticity Cu-Ni-Mn-Fe-Cr-Al copper-rich high-entropy alloy and its preparation method. The most significant feature of this alloy system is that, compared to conventional Fe-Co-Cr-Ni high-entropy alloys, it does not contain the expensive element Co, which helps reduce costs. Furthermore, it has a high Cu content, which helps improve the alloy's resistance to marine biofouling. Furthermore, it maintains a high copper content while still maintaining excellent tensile strength and plasticity.

[0024] The present invention reduces the content of elements such as Fe and Cr having positive mixing enthalpy with Cu, thereby achieving a microstructure composed of a stable FCC matrix and a small amount of BCC strengthening phase in the high entropy alloy.

[0025] The composition design of the alloy of the present invention comprehensively considers the effects of various elements on the microstructure, mechanical properties, corrosion resistance, and anti-biofouling properties of the alloy, resulting in the following beneficial effects:

[0026] (1) Compared with marine copper alloys, the high entropy alloy of the present invention has higher tensile strength and plasticity, reaching up to 831 MPa and 33% respectively. The high entropy alloy of the present invention has stronger seawater corrosion resistance;

[0027] (2) Compared with existing high entropy alloys, the high entropy alloy of the present invention has the highest copper content and therefore has better anti-biofouling potential;

[0028] (3) Compared with existing copper-containing high-entropy alloys, the high-entropy alloy of the present invention has excellent tensile strength and plasticity. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 1 is the XRD pattern of the alloy prepared in Examples 1-4 of the present invention.

[0030] Figure 2 1 is the room temperature tensile stress-strain curve of the alloy prepared in Examples 1-4 of the present invention.

[0031] Figure 3 1 is the polarization curve of the alloy prepared in Examples 1-4 of the present invention in 3.5 wt.% NaCl solution.

[0032] Figure 4 For example Cu of the present invention 48 Mn 10 Ni 24 Room temperature tensile stress-strain curves of Fe5Cr5Al8 high-entropy alloy after 50% cold rolling, solution treatment at 950℃ for 2h, and aging treatment at 450℃ for 6h. DETAILED DESCRIPTION

[0033] To further illustrate the present invention, the following examples further illustrate a high-strength, high-plasticity Cu-Ni-Mn-Fe-Cr-Al high-entropy alloy provided by the present invention. It should be understood that these examples are implemented based on the technical solutions of the present invention, and detailed implementation methods and specific operating procedures are provided only to further illustrate the features and advantages of the present invention, and do not limit the claims of the present invention. The scope of protection of the present invention is not limited to the following examples.

[0034] The present invention discloses a high-strength and high-plasticity copper-rich high-entropy alloy, the chemical formula of which is: Cu a Ni b Mn c Fe d Cr e Al f , among which, 40≤a≤55at%, 20≤b≤30at%, 5≤c≤15at%, 3≤d≤8, 3≤e≤8at%, 4≤f≤12at%, and a+b+c+d+e+f=100.

[0035] The chemical formula of the high entropy alloy is: Cu a Ni b Mn c Fe d Cr e Al f , among which, 40≤a≤50at%, 20≤b≤30at%, 6≤c≤10at%, 4≤d≤6at%, 4≤e≤6at%, 6≤f≤10at%, and a+b+c+d+e+f=100%.

[0036] A method for preparing the above-mentioned high entropy alloy, the method specifically comprising the following steps:

[0037] S1) weighing each raw material according to the designed ratio and pre-treating them for later use;

[0038] S2) putting the raw materials processed in S1) into a vacuum medium frequency induction melting furnace and evacuating the furnace to 1×10 -2 Pa below, smelting is carried out in an argon protective environment;

[0039] S3) After vacuum melting, use a crucible or a water-cooled copper mold to cast or suction cast the as-cast high entropy alloy, or a sample component of the desired shape and size;

[0040] S4) cold rolling the as-cast high-entropy alloy in S3) to control the thickness deformation, then performing crystallization annealing, and finally taking it out and water quenching to obtain a high-strength and high-plasticity copper-rich high-entropy alloy.

[0041] Said S4) further comprises subjecting the recrystallized high entropy alloy to aging treatment, and then taking it out for air cooling or water quenching, thereby obtaining a high-strength and high-plasticity copper-rich high entropy alloy.

[0042] The specific process of S1) is as follows: S1.1) firstly, the Cu, Ni, Mn, Fe, Cr, and Al metal raw materials are mechanically ground to remove the oxide scale on the surface of the elements;

[0043] S1.2) The metal raw material treated in S1.1) is placed in different containers and an alcohol solution is added thereto. The metal raw material is ultrasonically cleaned and then taken out and dried with the alcohol to obtain the ultrasonically treated metal raw material.

[0044] The thickness deformation of the cold rolling in S4) is 40-60%; the annealing temperature is 900-1000°C and the insulation time is 0.5-4h; the aging treatment temperature is 400-500°C and the insulation time is 4-24h.

[0045] The high-strength and high-plasticity copper-rich high-entropy alloy has an FCC+BCC dual-phase structure, a yield strength of 329 MPa, a tensile strength of 831 MPa, and an elongation of 33%.

[0046] A high-strength, high-plasticity copper-rich high-entropy alloy used in fields such as marine industry.

[0047] Example 1

[0048] A high-strength, high-plasticity copper-containing high-entropy alloy material, wherein the chemical composition of the high-entropy alloy is designed to be Cu 46 Ni 24 Mn 10 Fe5Cr5Al 10。

[0049] (1) Raw material preparation: Industrial-purity Cu, Ni, Mn, Fe, Cr, and Al elements were weighed and prepared according to molar percentage. Before preparation, pure Mn sheets were cleaned with 4% nitric acid aqueous solution to remove the surface oxide layer. All raw materials were ultrasonically cleaned and dried.

[0050] (2) Alloy smelting: Place the prepared raw materials into a copper crucible in a non-consumable vacuum arc furnace. Place Mn and Al elements at the bottom of the crucible, and then place the bulk Cu, Ni, and Fe on top of it. Close the furnace door and use a mechanical pump and a molecular pump to evacuate to 5×10 -3 Pa, fill with industrial pure argon to 0.05MPa. Before melting the alloy, first melt the Ti ingot to absorb the residual oxygen in the furnace, and then melt the alloy raw materials. In order to ensure the uniformity of the composition of the master alloy ingot, use a turning shovel to turn the alloy ingot over and melt it again after each melting. Each alloy ingot is melted at least 4 times to obtain a Cu with uniform composition. 46 Mn10 Ni 24 Fe5Cr5Al 10 Alloy ingots were cast into 10×10×50mm shapes using copper molds. 3 Test rod;

[0051] (3) Deformation heat treatment: The obtained as-cast high-entropy alloy test bars were cold rolled by 50% to obtain cold-rolled samples. The cold-rolled samples were placed in a box-type resistance furnace for solution treatment. When heated to 950°C, they were placed in the furnace and kept warm for 2 h. They were then taken out and water quenched.

[0052] (4) Microstructure detection: The microstructure of the solid solution high entropy alloy sample prepared in step (3) was detected by X-ray diffractometer. The results are shown in the attached figure. Figure 1 As shown. It can be seen that Cu 46 Mn 10 Ni 24 Fe5Cr5Al 10 The high entropy alloy has a FCC+BCC dual-phase structure in the solution treated state;

[0053] (5) Tensile performance test: CMT4105 universal tensile testing machine was used to test the Cu 46 Mn 10 Ni 24 Fe5Cr5Al 10 The tensile test of the sample of high entropy alloy solution treated at 950℃ for 2h was carried out, and its engineering stress-strain curve is shown in the figure. Figure 4 As shown in the figure, it can be seen that after solution treatment, the yield strength of the alloy is 329Mpa, the tensile strength is 648Mpa, and the elongation reaches 33%;

[0054] (8) Electrochemical performance test: Using Chenhua CHI604E electrochemical workstation, the Cu 46 Mn 10 Ni 24 Fe5Cr5Al 10 Polarization curves of high entropy alloys in the solution treated state at 950℃ are shown in the attached figure. Figure 3 The self-corrosion current density of high entropy alloy in solid solution is 4.7×10 -6 A / cm 2 The self-corrosion current density of nickel-aluminum bronze alloy is 1.9×10 -5 A / cm 2 , indicating that the high entropy alloy of the present invention has a lower corrosion rate;

[0055] (9) Cu ion permeation rate test: The samples after casting and solution treatment were immersed in 3.5wt.% NaCl solution for 2 days. The Cu ion content in the solution was then measured using an atomic absorption spectrometer. The Cu ion permeation rate of the alloy after solution treatment was 0.136mg / L / cm 2 , indicating that the high entropy alloy of the present invention has significant copper ion release ability and anti-biofouling potential in NaCl solution.

[0056] Example 2

[0057] A high-strength, high-plasticity copper-containing high-entropy alloy material, wherein the chemical composition of the high-entropy alloy is designed to be Cu 50 Mn 10 Ni 24 Fe5Cr5Al 6。 The preparation methods (1), (2) and testing methods are the same as those in Example 1.

[0058] (3) Deformation heat treatment: The obtained cast high entropy alloy test bar was cold rolled by 50% to obtain a cold-rolled sample. The cold-rolled sample was placed in a box-type resistance furnace for solution treatment. When heated to 950°C, it was placed in the furnace and kept warm for 2 h. Then it was taken out for water quenching. It was then placed in a box-type resistance furnace heated to 400°C and kept warm for 12 h for aging treatment. Then it was taken out and air-cooled.

[0059] (4) The results of tissue structure test are as attached. Figure 1 As shown, it can be seen that Cu 50 Mn 10 Ni 24 Fe5Cr5Al6 high entropy alloy has FCC+BCC dual-phase structure in the aging treatment state;

[0060] (5) The engineering stress-strain curve obtained from the tensile performance test is shown in the attached figure. Figure 2 As shown, it can be seen that Cu 50 Mn 10 Ni 24 After solution treatment at 950℃ for 2h and aging treatment at 400℃ for 12h, the Fe5Cr5Al6 high entropy alloy has a yield strength of 468MPa, a tensile strength of 775MPa, and an elongation of 30%.

[0061] (6) Electrochemical performance test of Cu in 3.5wt.% NaCl solution 50 Mn 10 Ni 24 The polarization curve of Fe5Cr5Al6 high entropy alloy in the aging treatment state is shown in the attached figure. Figure 3 As shown, the self-corrosion current density of the aged high entropy alloy is 1.2×10 - 6A / cm 2 The self-corrosion current density of nickel-aluminum bronze alloy is 1.9×10 -5 A / cm 2 , indicating that the high entropy alloy of the present invention has a lower corrosion rate.

[0062] Example 3

[0063] A high-strength, high-plasticity copper-containing high-entropy alloy material, wherein the chemical composition of the high-entropy alloy is designed to be Cu 48 Mn 10 Ni 24 Fe5Cr5Al 8。 The preparation methods (1), (2) and testing methods are the same as those in Example 1.

[0064] (3) Deformation heat treatment: The obtained cast high entropy alloy test bar was cold rolled by 50% to obtain a cold-rolled sample. The cold-rolled sample was placed in a box-type resistance furnace for solution treatment. When heated to 950°C, it was placed in the furnace and kept warm for 2 h. Then it was taken out for water quenching. It was then placed in a box-type resistance furnace heated to 450°C and kept warm for 6 h for aging treatment. Then it was taken out and air-cooled.

[0065] (4) The results of tissue structure test are as attached. Figure 1 As shown, it can be seen that Cu 48 Mn 10 Ni 24 Fe5Cr5Al8 high entropy alloy has a FCC+BCC dual-phase structure in the aging treatment state;

[0066] (5) The engineering stress-strain curve obtained from the tensile performance test is shown in the attached figure. Figure 2 As shown, it can be seen that Cu 48 Mn 10 Ni 24 After solution treatment at 950℃ for 2h and aging treatment at 450℃ for 6h, the yield strength of Fe5Cr5Al8 high entropy alloy is 606MPa, the tensile strength is 831MPa and the elongation reaches 13.7%.

[0067] (6) Electrochemical performance test of Cu in 3.5wt.% NaCl solution 48 Mn 10 Ni 24 The polarization curve of Fe5Cr5Al8 high entropy alloy in the aging treatment state is shown in the attached figure. Figure 3 As shown, the corrosion current density of the aged high entropy alloy is 2.51×10 - 6 A / cm 2 The self-corrosion current density of nickel-aluminum bronze alloy is 1.9×10 -5 A / cm2 , indicating that the high entropy alloy of the present invention has a lower corrosion rate.

[0068] Example 4

[0069] A high-strength, high-plasticity copper-containing high-entropy alloy material, wherein the chemical composition of the high-entropy alloy is designed to be Cu 46 Mn 10 Ni 24 Fe5Cr5Al 10。 The preparation methods (1), (2) and testing methods are the same as those in Example 1.

[0070] (3) Deformation heat treatment: The obtained cast high entropy alloy test bar was cold rolled by 50% to obtain a cold-rolled sample. The cold-rolled sample was placed in a box-type resistance furnace for solution treatment. When heated to 950°C, it was placed in the furnace and kept warm for 2 h. Then it was taken out for water quenching. It was then placed in a box-type resistance furnace heated to 400°C and kept warm for 12 h for aging treatment. Then it was taken out and air-cooled.

[0071] (4) The results of tissue structure test are as attached. Figure 1 As shown, it can be seen that Cu 46 Mn 10 Ni 24 Fe5Cr5Al 10 The high entropy alloy has a FCC+BCC dual-phase structure in the aging treatment state;

[0072] (5) The engineering stress-strain curve obtained from the tensile performance test is shown in the attached figure. Figure 2 As shown, it can be seen that Cu 46 Mn 10 Ni 24 Fe5Cr5Al 10 After solution treatment at 950°C for 2 hours and aging treatment at 400°C for 12 hours, the high-entropy alloy achieved a yield strength of 556 MPa, a tensile strength of 826 MPa, and an elongation of 24.4%.

[0073] (6) Electrochemical performance test of Cu in 3.5wt.% NaCl solution 46 Mn 10 Ni 24 Fe5Cr5Al 10 The polarization curve of high entropy alloy in the aging treatment state is shown in the attached figure. Figure 3 As shown, the self-corrosion current density of the aged high entropy alloy is 1.5×10 -6 A / cm 2 The self-corrosion current density of nickel-aluminum bronze alloy is 1.9×10 -5 A / cm 2 , indicating that the high entropy alloy of the present invention has a lower corrosion rate.

[0074] Example 5

[0075] A high-strength, high-plasticity copper-containing high-entropy alloy material, wherein the chemical composition of the high-entropy alloy is designed to be Cu 50 Ni 25 Mn 10 Fe5Cr5Al 5。 The preparation methods (1), (2) and tensile performance testing methods are the same as those in Example 1.

[0076] (3) Deformation heat treatment: The obtained cast high entropy alloy test bar was cold rolled by 40% to obtain a cold-rolled sample. The cold-rolled sample was placed in a box-type resistance furnace for solution treatment. When heated to 910°C, it was placed in the furnace and kept warm for 1 hour. Then it was taken out for water quenching. It was then placed in a box-type resistance furnace heated to 400°C and kept warm for 6 hours for aging treatment. Then it was taken out and air-cooled.

[0077] (4) After the aforementioned alloy preparation and deformation heat treatment, the alloy has a yield strength of 413 MPa, a tensile strength of 673 MPa, and an elongation of 27.3%;

[0078] Example 6

[0079] A high-strength, high-plasticity copper-containing high-entropy alloy material, wherein the chemical composition of the high-entropy alloy is designed to be Cu 48 Ni 24 Mn 10 Fe5Cr5Al 8。 The preparation methods (1), (2) and tensile performance testing methods are the same as those in Example 1.

[0080] (3) Deformation heat treatment: The obtained as-cast high-entropy alloy test bars were cold rolled by 60% to obtain cold-rolled samples. The cold-rolled samples were placed in a box-type resistance furnace for solution treatment. When heated to 990°C, they were placed in the furnace and kept at this temperature for 0.5 h. They were then taken out and water quenched.

[0081] (4) After the aforementioned alloy preparation and deformation heat treatment, the alloy has a yield strength of 460 MPa, a tensile strength of 787 MPa, and an elongation of 27.3%;

[0082] Example 7

[0083] A high-strength, high-plasticity copper-containing high-entropy alloy material, wherein the chemical composition of the high-entropy alloy is designed to be Cu 50 Mn 10 Ni 24 Fe5Cr5Al 6。 The preparation methods (1), (2) and tensile performance testing methods are the same as those in Example 1.

[0084] (3) Deformation heat treatment: The obtained cast high entropy alloy test bar was cold rolled by 40% to obtain a cold-rolled sample. The cold-rolled sample was placed in a box-type resistance furnace for solution treatment. When heated to 950°C, it was placed in the furnace and kept warm for 2 h. Then it was taken out for water quenching. It was then placed in a box-type resistance furnace heated to 400°C and kept warm for 24 h for aging treatment. Then it was taken out and air-cooled.

[0085] (4) After the aforementioned alloy preparation and deformation heat treatment, the alloy has a yield strength of 454 MPa, a tensile strength of 708 MPa, and an elongation of 21.1%;

[0086] The above describes in detail a high-strength, high-plasticity copper-rich high-entropy alloy, its preparation method, and its application provided in the embodiments of this application. The description of the above embodiments is only intended to help understand the method and core concept of this application; at the same time, those skilled in the art will find that the specific implementation methods and application scopes may vary based on the concept of this application. In summary, the contents of this specification should not be construed as limiting this application.

[0087] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different nouns to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. For example, "including" and "comprising" mentioned throughout the specification and claims are open-ended terms, so they should be interpreted as "including / including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problems within a certain error range and basically achieve the technical effects. The subsequent description in the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application, and is not intended to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the appended claims.

[0088] It should also be noted that the terms "include," "comprises," or any other variations thereof are intended to encompass non-exclusive inclusion, such that a product or system comprising a series of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such product or system. In the absence of further limitations, an element defined by the phrase "comprises a..." does not exclude the presence of other identical elements in the product or system comprising the element.

[0089] It should be understood that the term "and / or" as used herein is merely a description of the relationship between associated objects, indicating that three possible relationships exist. For example, "A and / or B" can represent: A exists alone, A and B exist simultaneously, or B exists alone. Furthermore, the character " / " in this document generally indicates that the associated objects are in an "or" relationship.

[0090] The above description shows and describes several preferred embodiments of the present application. However, as previously mentioned, it should be understood that the present application is not limited to the form disclosed herein and should not be construed as excluding other embodiments. Instead, the present application can be used in various other combinations, modifications, and environments and can be modified within the scope of the application concept described herein through the above teachings or techniques or knowledge in the relevant fields. Modifications and changes made by those skilled in the art do not depart from the spirit of the present application.

Claims

1. A high-strength, high-plasticity copper-rich high-entropy alloy, characterized in that: The chemical formula of the high entropy alloy is: Cu 46 Ni 24 Mn 10 Fe5Cr5Al 10 The yield strength of the alloy is 329 MPa, the tensile strength is 648 MPa, and the elongation reaches 33%. The high entropy alloy has a FCC+BCC dual-phase structure.

2. A high-strength, high-plasticity copper-rich high-entropy alloy, characterized in that: The chemical formula of the high entropy alloy is: Cu 50 Ni 24 Mn 10 Fe5Cr5Al6, the alloy has a yield strength of 468 MPa, a tensile strength of 775 MPa, and an elongation of 30%. The high entropy alloy has a FCC+BCC dual-phase structure.

3. A high-strength, high-plasticity copper-rich high-entropy alloy, characterized in that: The chemical formula of the high entropy alloy is: Cu 48 Mn 10 Ni 24 Fe5Cr5Al8, the alloy has a yield strength of 606 MPa, a tensile strength of 831 MPa, and an elongation of 13.7%. The high entropy alloy has a FCC+BCC dual-phase structure.

4. A method for preparing a high-strength, high-plasticity copper-rich high-entropy alloy as claimed in any one of claims 1 to 3, characterized in that: The preparation method specifically comprises the following steps: S1) weighing each raw material according to the atomic percentage in the chemical formula, pre-treating and setting aside; S2) Put the raw materials processed in S1) into a vacuum medium frequency induction melting furnace, and then evacuate to 1×10 -2 Pa, introduce argon gas for smelting; S3) casting or suction casting the high entropy alloy melted in S2) using a crucible or a water-cooled copper mold to obtain a cast high entropy alloy sample component of a desired shape and size; S4) The as-cast high entropy alloy in S3) is first cold-rolled to control the thickness deformation, then subjected to crystallization annealing, and finally taken out for water quenching to obtain a high-strength and high-plasticity copper-rich high entropy alloy.

5. The preparation method according to claim 4, characterized in that: The S4) also includes: performing an aging treatment on the high entropy alloy after the crystallization treatment, and then taking it out for air cooling or water quenching, so as to obtain a high-strength and high-plasticity copper-rich high entropy alloy; the aging treatment temperature is 400-500°C, and the insulation time is 4-24h.

6. The preparation method according to claim 4, characterized in that: The thickness deformation of the cold rolling in S4) is 40-60%; the annealing temperature is 900-1000°C, and the heat preservation time is 0.5-4h.

7. A high-strength, high-plasticity, copper-rich, high-entropy alloy prepared by the preparation method as described in any one of claims 4 to 6 is used in the marine industry.

Citation Information

Patent Citations

  • Copper-nickel-based medium-entropy alloy with excellent comprehensive mechanical properties and preparation method thereof

    CN113322396A